The Teaching English of English Grammar based on the 2013 Curriculum - Nurbiana Nurbiana (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
This study aims at investigating the teachers’ strategies in teaching English grammar based on the 2013 Curriculum.  The subject of this research  are two English  teachers at SMPN 11 Maros Baru. This study is conducted by qualitative design and is focused on the phenomenon method. The findings shows that the strategies applied by the teachers in teaching grammar based on the 2013 Curriculum are problem based learning, project and blended learning. meanwhile, the problems faced by the teachers when implementing the 2013 Curriculum are related to time, the learners’ selfconfident, the internet networking,  and the learning resources.  As the result, the findings elucidate that most of the teachers apply the 2013 Curriculum in their teaching process. although it was not deeply in the using. The teachers use discovery based learning, project based learning and problem based learning as the main strategy in their teaching and learning process. The problems faced by the English teacher when in implementing the 2013 Curriculum were related to time, the learners unconfident, the internet networking and the pedagogy technology competence.